2021
DOI: 10.1371/journal.pone.0256041
|View full text |Cite
|
Sign up to set email alerts
|

Factors impacting resilience as a result of exposure to COVID-19: The ecological resilience model

Abstract: Despite the severe psychological impact of the COVID-19 pandemic, some individuals do not develop high levels of psychological distress and can be termed resilient. Using the ecological resilience model, we examined factors promoting or hindering resilience in the COVID-19 pandemic. Of the 1034 participants (49.9±16.2 years; females 51.2%) from Italian general population, 70% displayed resilient outcomes and 30% reported moderate-severe anxiety and/or depression. A binary regression model revealed that factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
70
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(84 citation statements)
references
References 86 publications
10
70
3
1
Order By: Relevance
“…Although other research reports suggested that there is a relationship between a higher education level and anxiety during the pandemic [ 54 ], our findings suggest that lower education potentially may be a risk factor for greater sense of loss. Evidence suggesting that a lower level of education and lower socioeconomic status are associated with a higher level of anxiety, and a greater sense of loss during the pandemic has also been reported in other studies [ 44 , 69 ].…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Although other research reports suggested that there is a relationship between a higher education level and anxiety during the pandemic [ 54 ], our findings suggest that lower education potentially may be a risk factor for greater sense of loss. Evidence suggesting that a lower level of education and lower socioeconomic status are associated with a higher level of anxiety, and a greater sense of loss during the pandemic has also been reported in other studies [ 44 , 69 ].…”
Section: Discussioncontrasting
confidence: 84%
“…Longitudinal studies covering the years 2019–2021 and a few waves of the pandemic point to two phenomena that are important for our study. One of these relates to adaptation to the current situation observed in various populations despite the existing pandemic [ 53 , 54 ]. Effects of adjustment to “the new normal” include decreases in negative emotions as well as the characteristic features of post-traumatic growth, such as tendencies for increased reflectiveness, greater interest in spirituality and nature, and deeper relations with others [ 55 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, as evidenced in many studies on adults ( 44 , 65 68 ), even for children a key factor impacting the individual ability to cope with the distress caused by the pandemic could be linked to the personality aspect of resilience. More in particular, in the seven-dimension model of personality measured by the Temperament and Character Inventory (TCI) ( 69 ) or its junior version (jTCI) ( 64 ), high and low resilience profiles can be effectively measured by focusing on the two dimensions of harm-avoidance (a temperamental trait reflecting the tendency to avoid behaviors due to intense response to aversive stimuli expressed as fear of uncertainty, quick fatigability, shyness of strangers, and pessimistic worry) ( 70 ) and self-directedness (a character trait referring to self-determination, self-acceptance, responsibility and reliability, and to being able to control, regulate, and adapt behavior in accordance to one's own goals and values) ( 70 ), which are respectively negatively and positively related to resilience ( 71 73 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the UK and Republic of Ireland, we have demonstrated that a sizeable proportion (~65%) of the adult population has been highly resilient or have reported improvements in their mental health during the period first year of the pandemic [ 20 , 23 , 24 ], and that there were no changes in the prevalence estimates of (past two-week) non-suicidal self-injury or attempted suicide in the Republic of Ireland between May and August 2020 [ 25 ]. Research outputs from the Spanish and Italian surveys have also identified patterns of pandemic-related resilience and post-traumatic growth [ 26 , 27 ]. Collectively, this body of evidence refutes the popularly held view that the pandemic has caused a ‘tsunami’ of mental illness [ 28 ], and that the evidence suggests prevention efforts should focus on specific sub-groups of the population who have been particularly impacted by the pandemic.…”
Section: What Has the Study Found? Key Findings And Publicationsmentioning
confidence: 99%